HEALTH AWARENESS OF CORE LIFESTYLE BEHAVIORS DIET, SLEEP, AND PHYSICAL ACTIVITY AMONG YOUNG ADULTS IN JEDDAH, SAUDI ARABIA: A SYSTEMATIC REVIEW - Ghada Ahmed Abdullah, Fardous Mohamed Zhulmah, Azza Anas Abodawood, Samia Mohammed Alahdal, Sarah Talal Musallam (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Background: Young adults in Saudi Arabia are experiencing rapid lifestyle changes that may increase the risk of noncommunicable diseases, particularly through unhealthy diet, physical inactivity, and insufficient sleep.frontiersin+2​ Objective: To systematically synthesize evidence on health awareness and actual practices regarding diet, sleep, and physical activity among young adults in Jeddah, Saudi Arabia, using direct Jeddah data and closely related Saudi urban studies. Methods: A systematic search of PubMed, Google Scholar, and relevant national reports identified observational and interventional studies (2010–2025) assessing diet, sleep, physical activity, and related awareness in young adults (≈18–35 years), prioritizing Jeddah and the Makkah region, with other Saudi cities used for contextual comparison.pmc.ncbi.nlm.nih+3​ Results: Evidence from Jeddah adults and Saudi university students shows high prevalence of overweight/obesity, unhealthy diet (frequent fast food, low fruit/vegetable intake, skipping breakfast), physical inactivity, and short or irregular sleep. General awareness that unhealthy lifestyle contributes to obesity, diabetes, and cardiovascular disease is common, but detailed knowledge of recommendations (e.g., exercise duration, sleep hours) and translation into daily practice remain limited. Unhealthy behaviors tend to cluster, with physical inactivity, sedentary time, poor diet, and short sleep often co-occurring.pmc.ncbi.nlm.nih+9​ Conclusion: Young adults in Jeddah and similar Saudi urban settings exhibit a clear gap between health awareness and actual lifestyle behaviors in diet, sleep, and physical activity. City-specific, multi-component interventions aligned with national movement and lifestyle guidelines are needed to convert awareness into sustained healthy behaviors.pmc.ncbi.nlm.nih+3​